2020
DOI: 10.15835/nbha48111757
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll a fluorescence as an indicator of water stress in Calophyllum brasiliense

Abstract: The objective of this study was to evaluate chlorophyll a fluorescence as a stress indicator in Calophyllum brasiliense Cambess seedlings grown with different concentrations of abscisic acid (ABA) under intermittent water deficit condition: daily irrigation without ABA (I); daily irrigation + 10 μM ABA (I 10); daily irrigation + 100 μM ABA (I 100); suspension of daily irrigation without ABA (SI); suspension of daily irrigation + 10 μM ABA (SI 10) and  suspension of daily irrigation + 100 μM ABA (SI 100). The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…These strategies have been reported in the literature as a protective response in several species, for example in the seedlings of Callophyllum brasiliense Cambess. (Reis et al, 2020); these plants also had a smaller leaf area when subjected to water deficit, similar to those observed in the present study. We found that S. terebinthifolia plants were tolerant to water deficit for several days (1 st P0), maintaining a leaf area close to that of plants in the other treatments.…”
Section: Resultssupporting
confidence: 91%
“…These strategies have been reported in the literature as a protective response in several species, for example in the seedlings of Callophyllum brasiliense Cambess. (Reis et al, 2020); these plants also had a smaller leaf area when subjected to water deficit, similar to those observed in the present study. We found that S. terebinthifolia plants were tolerant to water deficit for several days (1 st P0), maintaining a leaf area close to that of plants in the other treatments.…”
Section: Resultssupporting
confidence: 91%
“…For (F 0 /F M ) the results are similar to those observed for other species considered tolerant to temporary water stress and with recovery potential after stress suspension. Thus, Reis et al (2020) for Calophyllum brasiliense under water deficit and Rosa et al (2018) for C. langsdorffii under flooding (during 42 days), observed similar results.…”
Section: Discussionsupporting
confidence: 61%
“…With the reduction of water availability in the soil, the growth characteristics of seedlings are reduced due to instability of the leaf metabolism and damage to the reaction centers of photosystem II (PS II) (Khatri & Rathore, 2019;Reis et al, 2020), impeding the initial formation. Environmental stress mitigation agents are required in these situations in order to maintain the quality of tree seedlings.…”
Section: Introductionmentioning
confidence: 99%